Utility of Cand PCR in the Diagnosis of Vulvovaginal Candidiasis in Pregnant Women - Eduardo García-Salazar; Paola Betancourt-Cisneros; Xóchitl Ramírez-Magaña; Hugo Díaz-Huerta; Erick Martínez-Herrera; María Guadalupe Frías-De-León (Journal of Fungi)
Vulvovaginal candidiasis (VVC) can lead to multiple complications when it occurs during pregnancy, so it is necessary to diagnose it promptly for effective treatment. Traditional methods for identifying Candida spp. are often too time-consuming and have limited specificity and sensitivity. In this work, we evaluated the diagnostic utility of an endpoint PCR assay (Cand PCR) in vaginal swab specimens. Using a cotton swab, 108 vaginal swab samples were taken from pregnant women who consented to participate in the study. The samples were inoculated in Sabouraud agar plates (the gold standard) and subsequently used to extract DNA directly from the exudate. The yeasts isolated from the Sabouraud agar were identified in CHROMagar™ Candida. DNA extracted from vaginal swabs was amplified by Cand PCR. Based on the results of the Cand PCR and the gold standard, sensitivity (S), specificity (E), positive predictive values (PPVs), and negative predictive values (NPVs) were determined. Cand PCR presented an S = 65%, E = 100%, PPV = 100% and NPV = 91%. Cand PCR showed low sensitivity for detecting Candida spp. directly from vaginal swabs, but it was useful for identifying the etiologic agent and reducing the time to obtain the result, which is usually at least 48 h.